The British Society for Genetic Medicine guidance on managing incidental findings identified during rare disease genomic testing. - Ellard,S; Hanson,H; Cassidy,E-J; Thomson,K; Durkie,M; Berry,I; Mann,K; Mein,R; Stals,K; Rankin,J; Taylor,RW; McVeigh,TP; et al. (J Med Genet, 2026)
BACKGROUND: Genomic testing will occasionally identify a highly actionable genetic variant or other finding that is not related to the reason for testing. Such incidental findings may be relevant to the patient undergoing testing or to their family members. METHODS: This guidance on managing incidental findings was developed by the British Society for Genetic Medicine to support clinicians requesting genomic tests and clinical scientists working in genomic laboratories within the National Health Service. RESULTS: Clinicians should include the possibility of incidental findings with a patient/parent(s) in discussions around genomic testing. Decisions regarding the reporting of a genetic variant unrelated to the referral reason will depend on clinical actionability, penetrance and the variant classification. Pathogenic variants may be reported if there is evidence of high penetrance and available treatment or surveillance that is likely to improve clinical outcome. Testing using large next generation sequencing gene panels and genome-wide array analysis increases the likelihood of revealing heterozygous carrier status for autosomal recessive disorders unrelated to the reason for testing. Reporting incidental heterozygous carrier status for autosomal recessive conditions is not recommended. CONCLUSION: This guidance provides a framework for the reporting of incidental findings with case examples and a cancer susceptibility gene list. Decision-making in accordance with guidelines will achieve greater consistency than case by case decisions. This guidance may be of use to healthcare professionals in other publicly funded healthcare systems with evolving genomic testing services.